The effects of cooperative learning on the classroom learning environment, attitude and self-esteem of students - Tran , Van Dat (Tạp chí Khoa học Trường Đại học Sư phạm Thành phố Hồ Chí Minh, 2019)
This experimental study investigated the effects of cooperative learning on the classroom learning environment, attitudes and self-esteem of 110 first-year primary education students toward the psychology subject over the eight weeks of instruction at An Giang University. The results showed that students who were instructed using cooperative learning perceived the classroom learning environment as more student-centered, cohesive and satisfied than did students who were instructed using lecture-based teaching. The results also reported that the experimental group had significantly higher scores than the control group on both scales of self-esteem and attitudes toward psychology.